Younger Children Develop Higher Effector Antibody Responses to SARS-CoV-2 Infection. (30th November 2022) - Tomasi, Lisa; Thiriard, Anais; Heyndrickx, Leo; Georges, Daphnée; Van den Wijngaert, Sigi; Olislagers, Véronique; Sharma, Shilpee; Matagne, André; Ackerman, Margaret E; Ariën, Kevin K; Goetghebuer, Tessa; Marchant, Arnaud
Abstract: Background: The basis of the less severe clinical presentation of coronavirus disease 2019 (COVID-19) in children as compared with adults remains incompletely understood. Studies have suggested that a more potent boosting of immunity to endemic common cold coronaviruses (HCoVs) may protect children. Methods: To test this hypothesis, we conducted a detailed analysis of antibodies induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children aged 2 months to 14 years. Results: Younger children had higher titers of antibodies to SARS-CoV-2 receptor binding domain (RBD), S1 but not S2 domain, and total spike (S) protein, higher avidity RBD immunoglobulin G, and higher titers of neutralizing and complement-activating antibodies as compared with older children. In contrast, older children had higher titers of antibodies to HCoVs, which correlated with antibodies to the SARS-CoV-2 S2 domain but not with neutralizing or complement-activating antibodies. Conclusions: These results reveal a unique capacity of young children to develop effector antibody responses to SARS-CoV-2 infection independently of their immunity to HCoVs.